Scrotal calculi - Artas, Hakan; Orhan, Irfan (Wiley, 2007)
Objective. Scrotal calculi are freely mobile calcified bodies lying between the layers of the tunica vaginalis of the testes. The etiology of scrotal calculi is unclear. They may develop as a sequela to hematomas or inflammatory changes within the scrotum or loose bodies from torsion and infarction of the appendix testis or epididymis. The aim of our series was to examine the etiopathogenesis of scrotal calculi, which were detected incidentally in various age groups, with reference to the medical literature. Methods. Among 868 patients, 23 (2.65%) cases of scrotal calculi were diagnosed on sonographic examinations. The ages of the patients ranged between 4 months and 65 years (mean age SD, 28.3 +/- 11.9 years). Results. On sonographic examination; we found a total of 51 scrotal calculi with a mean size of 4.22 +/- 2.42 mm (range, 2-10 mm) in 23 patients, an epididymal cyst in 3 patients (13%), epididymitis in 2 patients (8.6%), hydrocele in 3 patients (13%), varicocele in 3 patients (13%), and testicular microlithiasis in 1 patient (4%). Scrotal calculi were solitary in 11 patients and multiple in 12 patients. Conclusions. The prevalence of scrotal calculi was 2.65%, and a minority of patients had other abnormalities, reflecting the generally benign etiology of these pearls. To date, no information is available in the literature about the results of chronic irritation due to scrotal calculi. Further studies in larger series need to be performed to elucidate the formation mechanism and natural course of scrotal calculi.
Keywords: calculi; scrotum; sonography